CT IMAGING OF LIVER CYSTIC ECHINOCOCCOSIS - Begu, Aida; Jakimovska Dimitrovska, Maja; Bundovska Kocev, Smiljana; Jakimovski, Dragan (Македонско лекарско друштво = Macedonian medical association, 2025)
Liver cystic echinococcosis (CE) is a zoonotic disease caused by the accidental infection of humans with the eggs of the tapeworm Echinococcus granulosus. Two-thirds of all cases present with hepatic involvement.
Keywords: liver hydatid cyst; surgical treatment; Echinococcus granulosus